Aggregation Kinetics of Hematite Particles in the Presence of Outer Membrane Cytochrome OmcA of Shewanella oneidenesis MR-1 - Sheng, Anxu; Feng Liu; Shi, Liang; Juan* Liu (Environmental Science & Technology, 2016)
The aggregation behavior of 9, 36, and 112 nm hematite particles was studied in the presence of OmcA, a bacterial extracellular protein, in aqueous dispersions at pH 5.7 through time-resolved dynamic light scattering, electrophoretic mobility, and circular dichroism spectra, respectively. At low salt concentration, the attachment efficiencies of hematite particles in all sizes first increased, then decreased, and finally remained stable with the increase of OmcA concentration, indicating the dominant interparticle interaction changed along with the increase in the protein-to-particle ratio. Nevertheless, at high salt concentration, the attachment efficiencies of all hematite samples gradually decreased with increasing OmcA concentration, which can be attributed to increasing steric force. Additionally, the aggregation behavior of OmcA–hematite conjugates was more correlated to total particle–surface area than primary particle size. It was further established that OmcA could stabilize hematite nanoparticles more efficiently than bovine serum albumin (BSA), a model plasma protein, due to the higher affinity of OmcA to hematite surface. This study highlighted the effects of particle properties, solution conditions, and protein properties on the complicated aggregation behavior of protein–nanoparticle conjugates in aqueous environments.